Church Economy: Theoretical Basics and Empirical Analysis - Iliev, Petkan (Research Papers, 2017)
The business activity of religious organizations and their economic relations with other business agents (households, companies, the state) have been poorly studied but from a research perspective they represent an exceptionally interesting field for analysis. The purpose of this study is to substantiate the theoretical basics of church economy and do an empirical analysis on its functioning and its mechanism of action. At the same time, the study will also search for confirmation of the following research thesis: namely, that church economy is an important element of national economy, creating GDP and generating certain employment and as such, on the basis of existing theoretical concepts, we will define it and determine its components and peculiarities, which will serve for the creation of a methodological model of its measurement and evaluation.The categories of economics of religion and religious economics (economics of religious activity) have been defined on the basis of the theoretical-analytical approach, and the different in meaning term “church economy” has been introduced, which gives us the opportunity to encompass the overall religious activity in its social-economic aspect. The data about the social-economic activity of the church are, first and foremost, limited and unreliable. Official statistics collect a very limited circle of information about the activity of religious organizations. Despite this restrictive parameter, the first attempt in Bulgarian economic literature for a theoretical-empirical analysis of church economy has been made.